Vanadium-based oxide positive electrode material for aqueous zinc ion battery and preparation method of vanadium-based oxide positive electrode material

By using V6O13 or V6O13/VO2 composite materials as the positive electrode material of aqueous zinc ion batteries, the polyvalent state of vanadium ions is regulated for redox reaction, which solves the potential attenuation and structural collapse of vanadium-based oxides in AZIB, and achieves high energy density and excellent electrochemical properties.

CN119797425AActive Publication Date: 2025-04-11CHENGDU QUANYI INTELLECTUAL PROPERTY OPERATION CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510058342.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The application of vanadium-based oxides in aqueous zinc ion batteries is limited by electrostatic interaction, poor conductivity, vanadium dissolution problems, resulting in its potential attenuation and structural collapse, hindering its further development in AZIB.

Method used

Vanadium hexadiothio (V6O13) or V6O13/VO2 composite materials are used as the positive electrode material. By regulating the polyvalent state of vanadium ions, a variety of reversible redox reactions are carried out during the charge and discharge process, thereby improving the energy density, rate performance and cycling performance of the battery.

Benefits of technology

The high energy density, excellent rate performance and good cycle performance of vanadium-based oxide positive electrode material in aqueous zinc ion batteries are achieved, avoiding the problems of vanadium dissolution and structural collapse.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797425A_ABST
    Figure CN119797425A_ABST
Patent Text Reader

Abstract

The invention discloses a vanadium-based oxide positive electrode material for an aqueous zinc ion battery and a preparation method thereof.The vanadium-based oxide is a V6O13 or V6O13 / VO2 composite positive electrode material.The preparation method comprises the steps that S1, acetic acid is added into a faint yellow ammonium metavanadate solution to be mixed and stirred, the pH is adjusted to be 2-4, and a deep yellow solution is obtained; s2, transferring the deep yellow solution obtained in the step S1 into a polytetrafluoroethylene reaction kettle for high-temperature reaction, and cooling to obtain a green solid; s3, performing suction filtration and washing on the green solid obtained in the step S2 until the pH value is 6-6.5, and performing freeze drying until the weight is constant to obtain a precursor; and S4, grinding the precursor into powder, sintering in an argon atmosphere, and carrying out heat preservation, so as to obtain the product. The vanadium-based oxide aqueous zinc ion battery positive electrode material disclosed by the invention has valence diversity, excellent rate capability and relatively good cycle performance, the preparation method is simple, the cost is low, the yield is high, and conditions are easy to control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for aqueous zinc ion batteries, and in particular to a vanadium-based oxide positive electrode material for aqueous zinc ion batteries and a preparation method thereof. The vanadium-based oxide is hexavanadium trioxide (V6O 13 ) or vanadium trioxide / vanadium dioxide (V6O 13 / VO2) composite materials. Background Art

[0002] Among various energy storage devices, aqueous zinc-ion batteries (AZIBs) have shown their excellent competitiveness. The zinc anode used in AZIBs has several advantages, such as 820 mAh g -1 Ultra-high theoretical capacity, 5851 mAh mL -1 The extremely high energy density and low standard potential (-0.762 V vs. standard hydrogen electrode) of AZIB are the main features of AZIB. However, the shortage of cathode materials poses a challenge to the development of AZIB. Therefore, researchers are working on developing cathode materials with excellent performance, including transition metal oxides, Prussian blue analogs (PBA) and conductive polymers. Among them, vanadium-based oxides have the advantages of high theoretical capacity, diverse valence states and high electrochemical activity, and have been widely used as cathode materials for AZIB. However, the vanadium-based oxides and Zn 2+ There is a strong electrostatic interaction between them, poor conductivity, and inherent problems such as potential decay and structural collapse caused by the dissolution of vanadium, which hinders the further development of vanadium-based oxides in AZIB. By regulating the valence distribution of vanadium-based oxides, vanadium-based oxides can be optimized according to different application scenarios and needs, thereby meeting higher performance requirements. Therefore, exploring the regulation of the valence distribution of vanadium-based oxides is an important topic in the research of vanadium-based oxides. To this end, the present invention proposes a vanadium trioxide (V6O3) for aqueous zinc ion batteries. 13 )Cathode materials and V6O 13 The preparation method of / VO2 composite material utilizes the multivalent nature of vanadium ions to produce a variety of reversible redox reactions during the charge and discharge process of AZIB, which helps to improve the energy density, rate performance, and cycle performance of AZIB. Summary of the invention

[0003] The object of the present invention is to provide a vanadium-based oxide positive electrode material for aqueous zinc ion batteries and a preparation method thereof, wherein the vanadium-based oxide comprises hexavanadium trioxide (V6O 13 ) or V6O 13 / VO2 composite positive electrode material. The object of the present invention is achieved through the following technical solutions:

[0004] In a first aspect, the present invention provides a method for preparing a vanadium-based oxide positive electrode material for an aqueous zinc ion battery, wherein the vanadium-based oxide is V6O 13 or V6O 13 / VO2 composite positive electrode material, the preparation method thereof comprises the following steps:

[0005] S1. Add acetic acid to the light yellow ammonium metavanadate solution, mix and stir, and adjust the pH to 2-4 to obtain a dark yellow solution;

[0006] S2, transferring the dark yellow solution obtained in step S1 into a polytetrafluoroethylene reactor for high temperature reaction, and obtaining a green solid after cooling;

[0007] S3, filtering and washing the green solid obtained in step S2 to a pH value of 6-6.5 (to remove impurities in the green solid obtained in step S2 by acid washing), and freeze-drying to constant weight to obtain a precursor;

[0008] S4, grind the precursor into powder (place it in a porcelain boat and transfer it to a tube furnace), sinter and keep warm at 300℃~450℃ under argon atmosphere to obtain V6O 13 or V6O 13 / VO2 composite positive electrode material.

[0009] As some specific embodiments of the present invention, in step S4, when the sintering and heat preservation temperature is ≥300°C and <375°C, the obtained product is V6O 13 Cathode material;

[0010] And / or, when the sintering and heat preservation temperature is ≥375°C and ≤450°C, the obtained product is V6O 13 / VO2 composite positive electrode material.

[0011] As some specific embodiments of the present invention, in step S1, the concentration of the ammonium metavanadate solution is 0.02-0.04 mol / L.

[0012] As some specific embodiments of the present invention, in step S1, the preparation method of the ammonium metavanadate solution is: dissolving ammonium metavanadate in water, stirring at 20°C to 40°C for 30 to 60 minutes until the solution turns light yellow, thereby obtaining the ammonium metavanadate solution.

[0013] As some specific embodiments of the present invention, in step S1, the volume ratio of acetic acid to ammonium metavanadate solution is 1:5 to 10. The uniform nanorod shape of the present invention can be formed by using stable acetic acid to adjust the pH value of the solution to 2-4.

[0014] As some specific embodiments of the present invention, in step S1, the temperature of the mixing and stirring is 20°C to 40°C and the time is 30 to 60 minutes.

[0015] As some specific embodiments of the present invention, in step S2, the temperature of the high temperature reaction is 160°C to 200°C and the time is 8 to 12 hours.

[0016] As some specific embodiments of the present invention, in step S4, during sintering, the temperature is heated from 20°C to 40°C to 300°C to 450°C, and the heating rate is 2°C to 5°C / min.

[0017] As some specific embodiments of the present invention, in step S4, when heat preservation is performed, the heat preservation temperature is 300° C. to 450° C., and the heat preservation time is 3 to 4 hours.

[0018] As some specific embodiments of the present invention, the method for preparing the vanadium-based oxide positive electrode material specifically comprises the following steps:

[0019] (1) Weigh 1 mmol of ammonium metavanadate and dissolve it in 40 mL of water. Stir at room temperature for 30 minutes until the solution turns light yellow.

[0020] (2) 5 mL of acetic acid was added to the light yellow solution obtained in step (1), the pH was adjusted to 2-4, and stirred at room temperature for 40 minutes to obtain a dark yellow solution;

[0021] (3) The dark yellow solution obtained in step (2) was transferred into a 50 mL polytetrafluoroethylene reactor, and then the reactor was placed in an oven at 180 °C for 12 h; after the reactor was cooled to room temperature, a green solid sample was obtained, which was then filtered and washed until the pH value of the sample was greater than 6.5, and then freeze-dried to constant weight to obtain a precursor;

[0022] (4) The precursor obtained in step (3) was ground into powder, and then transferred to a tube furnace, heated from room temperature to 350 °C under an argon atmosphere at a heating rate of 5 °C / min, and kept at 350 °C for 3 hours to obtain V6O 13 or V6O 13 / VO2 composite positive electrode material.

[0023] In a second aspect, the present invention provides a vanadium-based oxide positive electrode material for an aqueous zinc ion battery, wherein the vanadium-based oxide is V6O 13 or V6O 13 / VO2 composite material, which is prepared by any of the methods described above.

[0024] Wu et al. (Journal of Alloys and Compounds 926 (2022) 166773) prepared V6O by hydrothermal reaction with vanadium pentoxide followed by aging. 13 As the positive electrode material of AZIB, the morphology is nanosheets and has the -1 At a high current density of 300 mA hg -1 The extremely high capacity at 0.3 A g -1 It maintains 421mA hg in 100 cycles -1 capacity, with a high capacity retention rate of 95%.

[0025] Selvam et al. (ACS Appl. Mater. Interfaces 2023, 15, 30350−30359) prepared V6O by hydrothermal reaction of ammonium metavanadate and thiourea (which has reducing properties) followed by argon annealing. 13 As the positive electrode material of AZIB, the morphology is layered nanosheets. -1 The specific capacity is 394 mAh g -1 At 2 A g -1 Under the current density cycle, its capacity retention rate is about 94% after 100 cycles, and the Coulomb efficiency is about 96%.

[0026] VO prepared by Xie et al. (ACS Appl. Mater. Interfaces 2024, 16, 8679−8687) x (V2O5 / V3O7 / V6O 13 Composite material) as AZIB positive electrode material, the morphology is irregular nanosheets, and its rate performance is 3A g -1 111.9mAh g -1 , cycle performance at 2A g -1 After 800 cycles, there is 142.4 mAh g -1 capacity.

[0027] The V6O of the present invention 13 and V6O 13 The morphology of the / VO2 composite positive electrode material is in the shape of nanorods, and as the positive electrode of AZIB, it has better rate performance and better cycle performance; the V6O 13 and V6O 13 / VO2 in rate performance test 5A g -1 The current density is 348.90 mAh g -1 and 168.48mAh g -1The battery specific capacity of the present invention is V6O 13 and V6O 13 / VO2 at 10A g -1 (High current density) Cyclic test of V6O 13 After 2000 cycles, the material still has a specific capacity of 190 mAhg -1 And with 100% Coulomb efficiency; while V6O 13 The peak discharge capacity of the / VO2 composite cathode material is 311.96 mAh g -1 And the capacity retention rate is close to 100% after 2000 cycles, so the present application can adapt to a larger current density and a larger number of cycles.

[0028] In the prior art CN111646460B, citric acid, oxalic acid, etc. are used as reducing agents, and mixed with ammonium metavanadate for reaction. Ammonium metavanadate or vanadium pentoxide will react with citric acid to form citric acid vanadium ion intermediates. In this process, the original vanadium ions will be reduced to lower-valent vanadium ions. The acetic acid used in the present invention is more inclined to act as a buffer, and generates acetate and vanadate with ammonium metavanadate, thereby generating low-valent vanadium ions. The synthesis method adopted is the hydrothermal method. Most of the vanadium oxides synthesized by the hydrothermal method are layered or flaky structures. The V6O synthesized by the invention 13 and V6O 13 / VO2 composite material is a nanorod structure. The prepared V6O 13 The crystallinity of the materials is not the same. In addition, the V6O prepared by the patented method 13 The material needs to be composited with graphene oxide to improve the electrochemical performance; and the V6O prepared by the present invention 13 and V6O 13 / VO2 as a positive electrode material for aqueous zinc ion batteries has good electrochemical properties. It does not need to be composited with graphene oxide, which can save costs to prepare high-performance positive electrode materials for aqueous zinc ion batteries. The present invention introduces oxygen vacancies by argon annealing. Although the method of the patent can also introduce oxygen vacancies, the area occupied by its oxygen vacancies is different from that of the oxygen vacancies in the present application, resulting in differences in performance between the two.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1) The method of the present invention has simple preparation process, low cost, high yield and easy control of preparation conditions;

[0031] 2) V6O prepared by the present invention 13 and V6O 13 / V2O5 composite positive electrode materials have valence diversity, and as positive electrode materials for aqueous zinc ion batteries, they have excellent rate performance and good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0033] Figure 1 V6O prepared in Example 1 13 SEM images of cathode materials;

[0034] Figure 2 V6O prepared in Example 2 13 SEM images of / VO2 composite cathode materials;

[0035] Figure 3 V6O prepared in Example 1 13 XRD pattern of positive electrode material;

[0036] Figure 4 V6O prepared in Example 2 13 XRD pattern of / VO2 composite cathode material;

[0037] Figure 5 XRD spectrum of the V2O5 / VO2 composite cathode material prepared in Comparative Example 2;

[0038] Figure 6 V6O prepared in Example 1-2 13 Cathode Materials and V6O 13 / VO2 composite cathode material rate performance diagram;

[0039] Figure 7 V6O prepared in Example 1-2 13 Cathode Materials and V6O 13 / VO2 composite cathode material cycle performance diagram;

[0040] Figure 8 This is a rate performance diagram of the New-AVO positive electrode material prepared in Comparative Example 1;

[0041] Fig. 9 This is a test diagram of the cycle performance of the New-AVO positive electrode material prepared in Comparative Example 1;

[0042] Fig.10 This is a rate performance diagram of the V2O5 / VO2 composite cathode material prepared in Comparative Example 2;

[0043] Fig.11 This is a test diagram of the cycle performance of the V2O5 / VO2 composite positive electrode material prepared in Comparative Example 2;

[0044] Fig.12 This is a photo of the green precipitate obtained in the solution when preparing the precursor in Example 1 and Example 2;

[0045] Fig.13 This is a physical photograph of the blue-black precipitate obtained in the solution when preparing the precursor in Comparative Example 1. DETAILED DESCRIPTION

[0046] The present invention will be further described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0047] Example 1

[0048] (1) Weigh 1 mmol of ammonium metavanadate and dissolve it in 40 mL of water. Stir at room temperature for 30 minutes until the solution turns light yellow.

[0049] (2) 5 mL of acetic acid was added to the light yellow solution obtained in step (1), and stirred at room temperature for 40 minutes to obtain a dark yellow solution.

[0050] (3) The dark yellow solution obtained in step (2) was transferred to a 50 mL polytetrafluoroethylene reactor, and then the reactor was placed in an oven at 180 °C for 12 h. After the reactor was cooled to room temperature, a green solid sample (such as Fig.12 The precursor was then filtered and washed until the pH value of the sample was greater than 6.5 and then freeze-dried to constant weight to obtain the precursor.

[0051] (4) The precursor obtained in step (3) was ground into powder, and then transferred to a tube furnace, heated from room temperature to 350 °C under an argon atmosphere at a heating rate of 5 °C / min, and kept at 350 °C for 3 hours to obtain V6O 13 Positive electrode material.

[0052] Example 2

[0053] (1) Weigh 1 mmol of ammonium metavanadate and dissolve it in 40 mL of water. Stir at room temperature for 30 minutes until the solution turns light yellow.

[0054] (2) 5 mL of acetic acid was added to the light yellow solution obtained in step (1), and stirred at room temperature for 40 minutes to obtain a dark yellow solution.

[0055] (3) The dark yellow solution obtained in step (2) was transferred into a 50 mL polytetrafluoroethylene reactor, and then the reactor was placed in an oven at 180 °C for 12 h. After the reactor was cooled to room temperature, a green solid sample was obtained, which was then filtered and washed until the pH value of the sample was greater than 6.5, and then freeze-dried to constant weight to obtain a precursor.

[0056] (4) The precursor obtained in step (3) was ground into powder, and then transferred to a tube furnace, heated from room temperature to 450 °C under an argon atmosphere at a heating rate of 5 °C / min, and kept at 450 °C for 3 hours to obtain V6O 13 / VO2 composite positive electrode material.

[0057] Electrochemical performance test: The V6O prepared in Example 1 13 Positive electrode material and V6O prepared in Example 2 13 / VO2 composite positive electrode materials were used as active materials, conductive carbon black (Super P) as conductive agent, and polyvinylidene fluoride (PVDF) as binder in a mass ratio of 7:2:1. After being mixed and ground evenly, they were transferred to a small bottle and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added. After stirring at room temperature for 8 hours, they were evenly coated on stainless steel foil. After vacuum drying at 80 °C for 12 hours, they were cut into circular electrode sheets with a diameter of 12 mm. The electrode sheets obtained after cutting were used as working electrodes, metal zinc as counter electrodes, glass fiber membranes (GF / D) as diaphragms, and 2.0 mol / L zinc sulfate as electrolytes. CR2025 button cells were assembled in air. The constant current charge and discharge performance of the battery was tested using the BTS-5V / 20mA charge and discharge tester of Shenzhen Xinwei Company, and the charge and discharge voltage range was 0.2~1.6 V. The current density of the rate performance test was 0.5A g -1 , 1 A g -1 , 2A g -1 , 3A g -1 , 5A g -1 , 10A g -1 . When testing the cycle performance, select 5 A g -1 or 10 A g -1 The current density was cycled up to 2000 times.

[0058] like Figure 1 As shown, V6O prepared in Example 1 13 SEM image of the positive electrode material. It can be seen from the figure that the V6O prepared in Example 1 13 The positive electrode materials are all composed of aggregated nanorods.

[0059] like Figure 2 As shown, V6O prepared in Example 2 13 SEM image of the V6O / VO2 composite positive electrode material. 13 / VO2 composite positive electrode materials are all composed of agglomerates of thinner and longer nanorods.

[0060] like Figure 3As shown, V6O prepared in Example 1 13 XRD spectrum of the positive electrode material. It can be seen from the figure that the main phase of the material prepared by the present invention is V6O 13 , and can correspond to the standard atlas.

[0061] like Figure 4 As shown, V6O prepared in Example 2 13 XRD spectrum of / VO2 composite positive electrode material. It can be seen from the figure that the main phase of the material prepared by the present invention is V6O 13 and VO2, and can correspond to the standard graph.

[0062] like Figure 6 As shown, V6O prepared in Example 1 13 Positive electrode material and V6O prepared in Example 2 13 / VO2 composite cathode materials at different current densities (0.5, 1, 2, 3, 5, 10A g -1 ) under the rate performance curve. It can be seen from the figure that the V6O prepared in Example 1 13 The positive electrode material has very good rate performance, among which, at 0.5 A g -1 , 1 A g -1 , 2 A g -1 , 3A g -1 , 5A g -1 and 10 A g -1 The charge / discharge specific capacity at the current density is 427.2 mAh g -1 / 419.74 mAh g -1 、398.65 mAh g -1 / 395.95 mAh g -1 、377.77 mAh g -1 / 376.6 mAh g -1 、365.76 mAh g -1 / 364.92mAh g -1 、348.90 mAh g -1 / 348.47 mAh g -1 and 315.28 mAh g -1 / 315.0 mAh g -1 ; V6O prepared in Example 2 13 / VO2 composite cathode material also has good rate performance, among which, at 0.5 A g -1 , 1 A g -1 , 2 A g -1 , 3A g -1 , 5A g-1 and 10 A g -1 The charge / discharge specific capacities at the current density are 279.67 mAh g -1 / 272.84 mAh g -1 , 240.68 mAh g -1 / 238.85 mAh g -1 , 206.62 mAh g -1 / 205.62 mAh g -1 、190.51 mAh g -1 / 189.76 mAh g -1 , 168.89 mAh g -1 / 168.48 mAh g -1 and 136.95 mAh g -1 / 136.67 mAh g -1 Therefore, the V6O of the present invention 13 Cathode materials and V6O 13 / VO2 composite positive electrode material has good charge and discharge reversibility, that is, excellent coulombic efficiency.

[0063] like Figure 7 As shown, V6O prepared in Example 1 13 Positive electrode material and V6O prepared in Example 2 13 / VO2 composite cathode material at 10A g -1 The cycle performance curve of the V6O prepared in Example 1 was cycled to 2000 cycles at the current density. 13 The positive electrode material has a high initial discharge specific capacity (291.65 mAh g -1 ) and good cycle stability; V6O prepared in Example 2 13 The peak discharge capacity of the / VO2 composite cathode material is 311.96 mAh g -1 And the capacity retention rate after 2000 cycles is close to 100%; therefore, the V6O 13 Cathode materials and V6O 13 / VO2 composite cathode material has good cycle performance.

[0064] Comparative Example 1

[0065] (1) Weigh 2.74 mmol of ammonium metavanadate and dissolve it in 40 mL of water. Stir at room temperature for 30 min until the solution turns light yellow.

[0066] (2) Weigh 4.6 mmol of citric acid and add it to the light yellow solution obtained in step (1). Stir at room temperature for 40 minutes to obtain a dark yellow solution.

[0067] (3) The dark yellow solution obtained in step (2) was transferred to a 50 mL polytetrafluoroethylene reactor, and then the reactor was placed in an oven at 180 °C for 12 h. After the reactor was cooled to room temperature, a blue-black precipitate (such as Fig.13 The precursor was then filtered and washed until the pH value of the sample was greater than 6.5 and then freeze-dried to constant weight to obtain the precursor.

[0068] (4) The precursor obtained in step (3) was ground into powder, and then transferred to a tube furnace, heated from room temperature to 350 °C under an argon atmosphere at a heating rate of 5 °C / min, and kept at 350 °C for 3 hours to obtain a product named New-AVO positive electrode material.

[0069] Figure 8 and Fig. 9 The figure shows the rate performance and cycle performance test of the material as the positive electrode material of aqueous zinc ion battery. It can be seen that compared with the V6O prepared by the present invention, 13 Cathode materials and V6O 13 / VO2 composite positive electrode material, the performance of this material is significantly poor, the charge / discharge specific capacity is low, and it has no research value.

[0070] Comparative Example 2

[0071] (1) Weigh 1 mmol of ammonium metavanadate and dissolve it in 40 mL of water. Stir at room temperature for 30 minutes until the solution turns light yellow.

[0072] (2) 5 mL of acetic acid was added to the light yellow solution obtained in step (1), and stirred at room temperature for 40 minutes to obtain a dark yellow solution.

[0073] (3) The dark yellow solution obtained in step (2) was transferred into a 50 mL polytetrafluoroethylene reactor, and then the reactor was placed in an oven at 180 °C for 48 h. After the reactor was cooled to room temperature, a green solid sample was obtained, which was then filtered and washed until the pH value of the sample was greater than 6.5, and then freeze-dried to constant weight to obtain the precursor.

[0074] (4) The precursor obtained in step (3) is ground into powder, and then transferred to a tube furnace, heated from room temperature to 350°C in an argon atmosphere at a heating rate of 5°C / min, and kept at 350°C for 12 hours to obtain a V2O5 / VO2 composite positive electrode material.

[0075] like Figure 5 The figure shows the XRD spectrum of the V2O5 / VO2 composite positive electrode material prepared in Comparative Example 2. As can be seen from the figure, the main phases of the material prepared in Comparative Example 2 are V2O5 and VO2, and they can correspond to the standard spectrum.

[0076] Fig.10 and Fig.11 The figure shows the rate performance and cycle performance test of the material as the positive electrode material of aqueous zinc ion battery. It can be seen that compared with the V6O prepared by the present invention, 13 Cathode materials and V6O 13 / VO2 composite positive electrode material, the charge / discharge specific capacity of this material is low and the performance is poor.

[0077] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.

Claims

1. A method for preparing a vanadium-based oxide positive electrode material for an aqueous zinc ion battery, characterized in that: The vanadium-based oxide is V6O 13 or V6O 13 / VO2 composite positive electrode material, the preparation method thereof comprises the following steps: S1. Add acetic acid to the light yellow ammonium metavanadate solution, mix and stir, and adjust the pH to 2-4 to obtain a dark yellow solution; S2, transferring the dark yellow solution obtained in step S1 into a polytetrafluoroethylene reactor for high temperature reaction, and obtaining a green solid after cooling; S3, filtering and washing the green solid obtained in step S2 to a pH value of 6-6.5, and freeze-drying to a constant weight to obtain a precursor; S4, grind the precursor into powder, sinter and keep warm at 300℃~450℃ in argon atmosphere to obtain V6O 13 or V6O 13 / VO2 composite positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step S4, when the sintering temperature is ≥300°C and <375°C, the obtained product is V6O 13 Cathode material; And / or, when the sintering and heat preservation temperature is ≥375°C and ≤450°C, the obtained product is V6O 13 / VO2 composite positive electrode material.

3. The preparation method according to claim 1, characterized in that: In step S1, the concentration of the ammonium metavanadate solution is 0.02-0.04 mol / L.

4. The preparation method according to claim 1 or 3, characterized in that: The preparation method of the ammonium metavanadate solution comprises: dissolving ammonium metavanadate in water, stirring at 20° C. to 40° C. for 30 to 60 minutes until the solution turns light yellow, thereby obtaining the ammonium metavanadate solution.

5. The preparation method according to claim 1, characterized in that: In step S1, the volume ratio of the acetic acid to the ammonium metavanadate solution is 1:5-10.

6. The preparation method according to claim 1, characterized in that: In step S1, the mixing and stirring is performed at a temperature of 20°C to 40°C and for 30 to 60 minutes.

7. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the high temperature reaction is 160°C to 200°C, and the time is 8 to 12 hours.

8. The preparation method according to claim 1, characterized in that: In step S4, during sintering, the temperature is heated from 20°C to 40°C to 300°C to 450°C, and the heating rate is 2°C to 5°C / min.

9. The preparation method according to claim 1, characterized in that: In step S4, when heat preservation is performed, the heat preservation temperature is 300° C. to 450° C., and the heat preservation time is 3 to 4 hours.

10. A vanadium-based oxide positive electrode material for an aqueous zinc ion battery, characterized in that: The vanadium-based oxide is V6O 13 or V6O 13 / VO2 composite material, which is prepared by the method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of zinc ion battery cathode material

    CN111646460A

  • Preparation method and application of vanadium tridecanoate electrode material for aqueous zinc ion battery

    CN114628680A

  • Preparation method and application of V2O5 / HxV2O5 composite positive electrode material

    CN118598186A

  • Nonaqueous electrolyte secondary battery

    JP1988013264A

  • Carbon matrix composite vanadium nitride NANO array, and preparation method therefor and use thereof

    WO2023236575A1